Small Interfering RNA (siRNA) of Mini circle DNA Transfection (McD) is Encapsulated by Gold Nanoparticles from Folate’s Receptors of Gold Conjugation as Curative Therapy for Non-Small’s Cell of Lung Cancer - agung wiwiek indrayani; I Gusti Ayu Sitti Sadvika; I Gede Wikania Wira Wiguna; Ni Putu Sri Indrani Remitha; I Gede Krisna Arim Sadeva; Anak Agung Bagus Putra Indrakusuma; Putri Ayu Wulandari; Ni Wayan Sucindra Dewi (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Lung cancer is one of the non-communicable diseases that have an increasing number of events that each year with a mortality rate of 18.4% and an incidence of 11.6%, occupies the top position based on GLOBOCAN data in 2018. One of management in the NSCLC is currently in the form of surgery and adjuvant therapy such as chemotherapy, radiotherapy and target therapy. However, there were weaknesses and limitations in care for its patients therefore development of curative therapy for NSCLC’s patients were needed.  The aim of this review is to learn and investigate about the potential of siRNA that is transfected into McD and folate receptors alpha-conjugated gold nanoparticle encapsulation as a therapeutic opportunity that could be developed as a treatment in management of NSCLC.Method: The writing method used in this review article was the study method of literature.  The used data comes from 45 of relevant literature sources and was arranged systematically in accordance with the topic of the problem discussed, along with the inclusion and exclusion criteria.Result: This treatment could increase gene transfection, siRNA biodistribution in organs, reduced KRAS, Bcl-2, and VEGF expression.  Moreover, siRNA had entered phase III clinical trials and FOLR1 antibodies were in phase II of clinical trials.Conclusion: Utilization of siRNA specifically was designed for three genes such for KRAS, VEGF and Bcl-2 which were three genes that played a role in the pathogenesis of NSCLC, could be the right modality choice for treatment of NSCLC.